How do current and past mining activities affect water security, health, and economic opportunities? - Frempong, Raymond Boadi; Stadelmann, David; Thiam, Djiby Racine (Applied Economic Perspectives and Policy, 2025)
This paper investigates the effect of mining activities on health care, income and water deprivations in Africa. By combining household data with mining locations, we conducted an econometric analysis to assess the impact of mining on self-reported water security, health, and economic opportunities for 142,838 households. Our study utilizes the presence of active and inactive mines to measure the effects of household exposure to mining activities. We observe that proximity to active mining sites is associated with self-reported improved water security, access to health, and economic opportunities. Instrumental variable estimates support a causal interpretation of our results. Specifically, households located within a 50?km radius of active mines reported a 4% lower probability of lacking clean water. Our findings also reveal that robust local institutions not only enhance water security but also mitigate the negative health impacts associated with mine closures. These results suggest that strengthening local governance can amplify the potential benefits of mining operations. Therefore, we recommend the strengthening of local government institutions to foster the resilience of vulnerable mining communities.
Keywords: Africa; Health; Livelihood; mining; poverty; WASH